Temperature dependence of twinning and magnetic stresses in Ni46Mn24Ga22Co4Cu4 alloy with giant 12% magnetic field-induced strain. (1st April 2017) - Sozinov, A.; Soroka, A.; Lanska, N.; Rameš, M.; Straka, L.; Ullakko, K.
Abstract: We study magnetic shape memory alloy Ni46 Mn24 Ga22 Co4 Cu4 showing up to 12% magnetic field-induced strain (MFIS). The MFIS is mediated by motion of the compound twin boundaries (CTBs) in non-modulated tetragonal crystal lattice. We present temperature dependences of the twinning stress σ TW ( T ), tetragonality ratio, and magnetic anisotropy energy density K U ( T ), used for magnetic stress σ MAG ( T ) calculations. With temperature increasing, the twinning stress for CTBs decreases with the slope of ‐0.02 MPa/K, twice slower than observed for type I twin boundaries in 10M Ni-Mn-Ga martensite. We found and explained existence of temperature window, within which the giant MFIS is observed. Graphical abstract: